High-temperature corrosion behavior of high-temperature and high-pressure cavitation processed Cr–Mo steel surface. Issue 8 (August 2020) - Ijiri, Masataka; Ogi, Takayuki; Yoshimura, Toshihiko
Abstract: In this paper, long-term high-temperature corrosion at 500 °C and high-temperature corrosion at the melting temperature of a corrosive ash mixture were examined because the use of high-temperature equipment such as boilers and gas turbines increases year over year. To investigate the optimum cavitation processing conditions for the specimens used in high-temperature corrosion tests, the surface properties of each processed specimen were examined. In specimens processed using multifunction cavitation (MFC), the compressive residual stress was high when the processing time was 10 min and the Cr content on the surface was greater than on the surface of an unprocessed specimen. On the other hands, in specimens subjected to water-jet peening (WJP), the compressive residual stress was high when the processing time was 10 min. In the present study, the processing time was selected to be 10 min and all high-temperature corrosion tests were conducted by the coating method. In the case of long-term high-temperature corrosion at 500 °C, the corrosion loss of the MFC-processed and WJP-processed specimens was small, whereas the corrosion loss of the unprocessed specimen was large. Abstract : Materials science; Mechanical engineering; Coatings; Metals; Materials characterization; Materials processing; Materials property; Water jet peening; Multifunction cavitation; Hot corrosion; Thermal stress cycle; Cr–Mo steel; Coating test.